A Study of Teacher Professionalism in Online Learning Based on School Accreditation in Vocational High School - Mhd Syafiq Adzkia; Fauzi Rahman; Miranda Putri Simatupang; Niswardi Jalinus; Hansi Effendi (Universitas Muhammadiyah Enrekang, 2022)
The problem in this study is that teacher professionalism is still low, the majority of teachers are less able to adapt to the skills of 21st century teachers, there is a lack of teacher motivation in improving self-quality due to not being able to compete and not being prepared to keep up with the times, and there is a lack of teacher ability to apply 21st century skills. at SMK Negeri 2 Sungai Penuh. The purpose of this study is to determine how the accreditation of SMK Negeri 2 Sungai Penuh influences the professionalism of teachers in online learning. The research method employed is a combination of quantitative and qualitative techniques. The population of this study consisted of 95 TITL class X students. The sample size for this study was 95 individuals. Total sampling is used as the sampling method. Descriptive data analysis is employed, and Respondent's Level of Achievement is measured (TCR). The results indicated that the professionalism of teachers on the indicator of digital age literacy was 45.71 percent, with an incorrect interpretation. An incorrect interpretation yielded a value of 46.92% for the indicator of inventiveness. On the indicator of effective communication, a poor interpretation yielded a value of 46.92%. With improper interpretation, a value of 48.07 percent was obtained for the indicator of high productivity. Overall, the professionalism of the instructor received a score of 46.90% for a poor interpretation. On the basis of SMKN 2 Sungai Penuh school accreditation, it can be deduced that the professionalism of teachers in online learning has been misconstrued.